A Comparative Analysis of Resilience of Islamic and Conventional Banks in Indonesia - Sri Ulina; M. Shabri Abd. Majid (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
The presence of the 2008 Global Financial Crisis (GFC) has adversely impacted both conventional and Islamic banking performances. This study aims to empirically compare the ﬁnancial performances between Islamic banks and conventional banks during the pre- and post-2008 GFC periods. It also attempts to compare the ﬁnancial performance of each Islamic and conventional bank between the pre- and post-2008 GFC periods. Three state-owned banks from each conventional and Islamic banking category were selected as the study sample using the purposive sampling technique. Based on the independent sample t-test, the study found a signiﬁcant diﬀerence between the Islamic and conventional banking performances during the pre- and post-2008 GFC periods. Meanwhile, based on the paired t-test, the decline in Islamic banking performance from the pre-2008 GFC to the post-2008 GFC periods was signiﬁcantly smaller than their conventional banking counterparts. These ﬁndings show the Islamic banks' superiority over their conventional banking counterparts due to fair and just practices based on Islamic tenets. Due to theirreliance in facing the episodes of crises, the Islamic banks deserve a strong support by government by enhancing prudent Islamic banking regulation. The Islamic banks should strive to operate fully based on the shari'ah principles and prudent banking management.